Konstitusionalisme Digital: Membangun Kerangka Hukum untuk Tata Kelola Penyelenggaraan Negara di Era Teknologi - Muhammad Khaidir Kahfi Natsir; Magdhalena Tasik Todingrara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
In an ever-evolving digital era, the protection of human rights has become an increasingly complex and urgent challenge. Digital constitutionalism emerges as an innovative and necessary framework to address this challenge, integrating human rights principles into technology-based state governance. This journal aims to explore how digital constitutionalism can strengthen the protection of human rights while analyzing the challenges and opportunities faced in its implementation. Through a qualitative analysis approach, this research collects and analyzes relevant literature as well as case studies from various countries that have adopted the principles of digital constitutionalism. The findings indicate that while digital constitutionalism offers significant potential to enhance human rights protection, substantial challenges such as privacy, data security, and access to information still need to be addressed. Furthermore, the role of government, civil society, and the private sector is crucial in creating an environment that supports the protection of human rights in the digital space. The conclusion of this research emphasizes the importance of cross-sector collaboration to ensure that human rights are not only constitutionally recognized but also effectively protected in practice. Thus, digital constitutionalism serves not only as a tool for safeguarding human rights but also as a driver for creating a more transparent, accountable, and responsive governance system to meet the needs of society in the digital era.